Sistema digital y la gestión turística hotelera en la ciudad de Quevedo año 2019 - Vera Cedeño, Jordan Olmedo (2020)
At present it is planned that the reasons why companies need to be certified with quality is to satisfy the customer in full with the desired level and be on par with competitiveness, so they focus on finding new ways of satisfaction with innovation. Certifications for tourist establishments promote safety and importance, much better now that the TICS for monitoring and processing them are established taking into account ISOO 9001 quality and QUALITY regulations or in turn, certifying stars between 2 and 5 mentions. the time the digital certification is still seen in an unconventional way since it simulates insecurity on the part of the tourist establishments, what is not visualized is that the online method contributes significantly in the labor growth by departments and improves the performance of customer service For this reason, it was implemented as a general objective to design a digital system to promote quality development while minimizing efforts in doing so.